Peradilan Berpancaran “Sinar Ketuhanan”: Mahkamah Konstitusi Dalam Masa Kepemimpinan Arief Hidayat (2015-2017) - Bisariyadi Bisariyadi (Fakultas Hukum Universitas Islam Indonesia, 2020)
Almost every Chief Justice of the Constitutional Court has jargon carried during theis leadership. Arief Hidayat, during his reign, often put forward the term